Comparing Face-to-Face, Emergency Remote Teaching and Smart Classroom: A Qualitative Exploratory Research Based on Students’ Experience during the COVID-19 Pandemic - Josep Petchamé (Sustainability, 2021)
The COVID-19 pandemic significantly disrupted traditional face-to-face teaching worldwide and forced education institutions to adopt new, online teaching formats to enable students to continue with their studies. This research focuses on students’ perceptions of three teaching different modalities: face-to-face (F2F), Emergency Remote Teaching (ERT) and Smart Classroom (SC), which were implemented in response to the restrictions enforced to combat the spread of COVID-19. A qualitative study based on two user experience techniques, Pocket Bipolar Laddering and Emotional Appraisal, was carried out on a group of second-year ICT engineering university students at La Salle Campus Barcelona. The former technique consists in identifying a maximum of three positive and three negative salient items, while the latter is intended to rate pairs of opposite feelings. In the SC format, saving time on travel to university was considered an advantage of online learning, while disadvantages included less effective instructor–student interaction, distractions when off-campus and teamwork issues. These shortcomings can be addressed by specific online teaching training to develop a more active form of learning and foment student participation. However, both ERT and SC modalities were considered effective solutions to cope with the social and mobility restrictions imposed during the pandemic.